Time-varying stiffness characteristics of roller bearing influenced by thermal behavior due to surface frictions and different lubricant oil temperatures. (April 2020) - Hao, Xu; Zhai, Jingyu; Liang, Junshuai; Chen, Yitong; Han, Qingkai
Abstract: In this paper, the time-varying stiffness of the cylindrical roller bearing due to the thermal behavior, i.e. warm-up process and different lubricant oil temperatures are experimentally investigated. Firstly, a special test rig that can measure the bearing stiffness is built. Then, a bearing stiffness identification method is proposed, which can avoid the influence of the clearance and deformation on measurement results. Finally, a series of measurements are carried out at different operational conditions. Results reveal that the bearing stiffness shows strong nonlinearity and time-varying characteristics due to the variation of structure and oil performance. In startup (quasi-isothermal condition) and thermal balance states (combined with the frictional heat generation), the influence of the rotational speed on stiffness is opposite. Highlights: A stiffness identification method for bearing with internal clearance is proposed. The effect of thermal behavior on bearing stiffness characteristics is studied. The bearing stiffness decreases sharply during the warm-up and oil heating. The effect of speed on stiffness in startup and thermal balance state is opposite.